Denominational Loyalty on the Cooperative Programme of the Nigerian Baptist Convention Between (2013-2023) - Musa, Emmanuel Ubandoma; Afolaranmi, Adebayo Ola (Eximia, 2024)
The Baptist Cooperative Programme is a system in which churches, who cooperate with the Nigeria Baptist Convention (NBC), make contributions in the form of certain percentages of their tithes, offerings, and undesignated income to their associations, state conferences, and the national body. This paper explores the effects of denominational loyalty on the Cooperative Programme of the Nigerian Baptist Convention (NBC) and strategies to deepen this loyalty among church members. Social identity theory suggests that individuals define themselves based on their membership in social groups, leading to the formation of an identity that is partly derived from their group membership. The decline in the commitment of churches within this period of ten years is worrisome. The existing problem lies in the need to strengthen denominational loyalty to the Convention amidst changing societal dynamics and competing religious influences. Using secondary sources of data collection, including scholarly articles, books, and Convention reports, this study analyses the historical context and current practices of the Baptist Cooperative Programme. Preliminary findings suggest that the Cooperative Programme plays a crucial role in fostering a sense of belonging and loyalty among members, contributing to the overall growth and sustainability of the denomination. Also, while there is a strong desire for cooperation among Baptist Churches, challenges such as lack of loyalty, proper communication, and financial constraints hinder the commitment of the members. The study concludes that the Baptist Cooperative commitment has the potential to strengthen denominational loyalty among Baptist churches in Nigeria. Hence, by addressing these challenges and building on the potential successes of the Cooperative Programme, the Nigerian Baptist Convention can further enhance unity and cooperation among its member churches, ultimately strengthening the denomination as a whole.